2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610346
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of malaria in Giemsa-stained thin blood smears

Abstract: The current gold standard of malaria diagnosis is the manual, microscopy-based analysis of Giemsa-stained blood smears, which is a time-consuming process requiring skilled technicians. This paper presents an algorithm that identifies and counts red blood cells (RBCs) as well as stained parasites in order to perform a parasitaemia calculation. Morphological operations and histogram-based thresholding are used to extract the red blood cells. Boundary curvature calculations and Delaunay triangulation are used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Algorithmic, computer-based detection and diagnosis of malaria is the subject of continuing research [41][42][43][44][45], and could aid in the implementation of these new technologies by lowering barriers to adoption and increasing access to care. However, an intriguing concept has been recently developed that combines the power of digital imaging with human ingenuity.…”
Section: Malaria and Other Blood-borne Parasitesmentioning
confidence: 99%
“…Algorithmic, computer-based detection and diagnosis of malaria is the subject of continuing research [41][42][43][44][45], and could aid in the implementation of these new technologies by lowering barriers to adoption and increasing access to care. However, an intriguing concept has been recently developed that combines the power of digital imaging with human ingenuity.…”
Section: Malaria and Other Blood-borne Parasitesmentioning
confidence: 99%
“…Author Suryawanshi et al [39] performed image binarization by using Poisson distribution based minimum error threshold value. Authors Mushabe et al [40], Damahe et al [41] used Zack thresholding method on the 'V' or 'value' component of HSV image for segmentation. Authors Purwar et al [42] have used Active Contour model for segmentation of red blood cells.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors Nugroho et al [24] used K-NN classifier with 'S component' in HSV colour space for segmentation. Mushabe et al [40] used K-NN classifier to identify the parasite and non-parasite regions. Nasir et al [48], used the saturation channel of image in HSI colour space and moving Knearest neighbour (MKNN) to differentiate parasite containing red blood cell.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently RGB pixel information‐based malaria diagnosis using Bayesian classifier was reported in Mushabe et al . (). Based on this extensive literature survey, it is observed that so far the maximum number of microscopic features (= 83) is considered by Tek et al .…”
Section: Introductionmentioning
confidence: 99%
“…Circle-ellipse fitting search algorithmbased malaria diagnosis was reported recently (Sheikhhosseini et al, 2013). Recently RGB pixel information-based malaria diagnosis using Bayesian classifier was reported in Mushabe et al (2013). Based on this extensive literature survey, it is observed that so far the maximum number of microscopic features (= 83) is considered by Tek et al (2010) for malaria detection based on lesser sample size.…”
Section: Introductionmentioning
confidence: 99%